Impact of rice seed production, processing, and distribution training on the stakeholders in Bangladesh - Tani, Tanzina Tazmim; Afrad, Md. Safiul Islam; Prodhan, Foyez Ahmed; Khan, Md. Arifur Rahman; Habib, M. Ashraful; Nayak, Swati; Islam, Saidul; Manik, Md. Nazmul; Rahman, Md. Mahbubur; Biswas, Amlan; Wadud, Fatema; Mann, Stephan (Sciencedomain International, 2023)
The study examined the impact of rice seed production, processing, and distribution training on the rice seed stakeholders. Ten one-day training events were conducted by Bangladesh Agricultural Development Corporation (BADC) and funded by the International Rice Research Institute (IRRI). Sample size of trainees included 199 rice seed dealers, 62 rice growers, and 29 dealers cum growers across four divisions of Bangladesh. The perceived impact of training was determined by employing a t-test. Almost all of the stakeholders showed improvement in their learning of the subjects designed and the correlation between their knowledge before and after training sessions were highly correlated.. Dealers expressed their views of moderate use of the training outcomes in determining seed demand, storage, and sale, whereas growers and dealer cum growers were highly optimistic about using their knowledge and skills obtained in seed production, processing, storing, and marketing in a better way. Significant changes in knowledge and skills and favorable perceptions were observed among all the stakeholders for better production, processing, and utilization of rice seed.